+0  
 
+1
337
2
avatar+168 

Given f(x)=3x^2 +9x and g(x) = x^2 - x -12, find (f/g) (x). 

 

also

 

when given f(x) =x^2 -3x + 7 and g (x) = x+3, solve f(x) = g(x)

 Mar 18, 2019
 #1
avatar+1181 
0

Second one:

 

x^2-3x+7=x+3

x^2-4x+4=0

(x-2)^2=0

x=2

 

You are very welcome!

:P

 Mar 18, 2019
 #2
avatar+111432 
+1

Given f(x)=3x^2 +9x and g(x) = x^2 - x -12, find (f/g) (x). 

 

(f / g) (x)   means  f(x) / g(x)......so

 

3x^2 + 9x                   3x  ( x + 3)                   3x

____________=      ____________  =      ______          [ x not equal to -3, or 4 ]

x^2 - x - 12                (x - 4)( x + 3)              x -  4

 

 

Second one

 

f(x)  = g(x)

 

x^2 - 3x + 7  =  x + 3             subtract x + 3 from both sides

 

x^2 - 4x + 4  =  0                factor

 

(x - 2)^2 = 0                      take the square root

 

x - 2 = 0                              add 2 to both sides

 

 x = 2

 

 

 

 

cool cool  cool

 Mar 18, 2019

11 Online Users